New Viruses in Idiopathic Human Diarrhea Cases, the Netherlands - Saskia L. Smits; Claudia M.E. Schapendonk; Janko van Beek; Harry Vennema; Anita C. Schürch; Debby Schipper; Rogier Bodewes; Bart L. Haagmans; Albert D. M. E. Osterhaus; Marion P. Koopmans (Emerging Infectious Diseases, 2014)
Emerging viral infections can be identified by using a viral metagenomics approach for clinical human material. Diarrhea samples of patients with unexplained gastroenteritis from the Netherlands were analyzed by using viral metagenomics. Novel circular DNA viruses, bufaviruses, and genogroup III picobirnaviruses were identified. These data expand our knowledge of the human virome.